AKTIVITAS BIOLARVASIDA EKSTRAK DAUN JERUK NIPIS (Citrus aurantifolia) TERHADAP LARVA NYAMUK Culex sp - Siska Musiam; Agus Ariyanto; Noverda Ayuchecaria (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Lymphatic filariasis (elephantiasis) is a disease caused by filarial worms transmitted by the Culex sp. Handling this disease can be done by breaking the chain of spread by killing off the Culex sp larvae. Flavonoids, saponins, tannins, and limonoids are chemical compounds that can damage mosquito larvae. Lime leaves (Citrus aurantifolia) have been known to contain these compounds. The aim of this study was to examine the activity of extract of lime leaves on Culex sp. The extracts used were concentrations of 0.25%, 0.50%, 1.00%, and 1.50%, plus temephos 1% as a positive control, and tap water as a negative control. Each test was carried out on 20 Culex sp Instar III larvae observed for 24 hours with 4 repetitions. The results showed that the effective concentration that killed as much as 50% of Culex sp (LD50) mosquito larvae was 0.948%.